EVALUASI PENERAPAN SISTEM PENGENDALIAN INTERNAL PADA SIKLUS PENDAPATAN : PENERIMAAN PESANAN HINGGA PENERIMAAN KAS DENGAN MENGGUNAKAN COSO INTERNAL CONTROL FRAMEWORK DI CV. ASRI MADINAH PASURUAN - Yanuardo Yudo Persian; Adhicipta Raharja Wirawan (Perpustakaan Universitas Surabaya, 2016)
This study aims to determine the accuracy of the use of the internal control system in order to improve the effectiveness and efficiency of the revenue cycle CV. Asri Madinah. Beside that, this study also aims to determine how is the appropriateness internal control system in accordance with the COSO internal control framework, and how to manage the proper revenue cycle. This study are included in the explanatory research that aims to obtain an explanation of the internal control system and accounting information systems problems in the revenue cycle of CV. Asri Madinah. From the research results, it was found that the working internal control system is still not fully implemented in the standards set by the COSO Internal Control Framework. It also affects the quality of the revenue cycle activities. Potential of lossing income, security, failure to obtain effectiveness and efficiency in processing the orders, potential loss by the canceled order, and the other related problems that are found in this study.